Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet is associated with lower presence of non-alcoholic fatty liver disease in middle-aged and elderly adults. Issue 4 (30th March 2020) - Xiao, Mian-Li; Lin, Jie-Sheng; Li, Yi-Hong; Liu, Meng; Deng, Yun-Yang; Wang, Chang-Yi; Chen, Yu-Ming
Abstract: Objective: Previous studies have shown that the Dietary Approaches to Stop Hypertension (DASH) diet might contribute to managing risk factors of non-alcoholic fatty liver disease (NAFLD), but evidence is limited. We examined the association of DASH diet score (DASH-DS) with NAFLD, as well as the intermediary effects of serum retinol-binding protein-4 (RBP4), serum high-sensitivity C-reactive protein (hs-CRP), serum TAG, homeostasis model assessment of insulin resistance (HOMA-IR) and BMI. Design: We performed a cross-sectional analysis of a population-based cohort study. Dietary data and lifestyle factors were assessed by face-to-face interviews and the DASH-DS was then calculated. We assessed serum RBP4, hs-CRP and TAG and calculated HOMA-IR. The presence and degree of NAFLD were determined by abdominal sonography. Setting: Guangzhou, China. Participants: Guangzhou Nutrition and Health Study participants, aged 40–75 years at baseline ( n 3051). Results: After adjusting for potential covariates, we found an inverse association between DASH-DS and the presence of NAFLD ( P trend = 0·009). The OR (95 % CI) of NAFLD for quintiles 2–5 were 0·78 (0·62, 0·98), 0·74 (0·59, 0·94), 0·69 (0·55, 0·86) and 0·77 (0·61, 0·97), respectively. Path analyses indicated that a higher DASH-DS was associated with lower serum RBP4, hs-CRP, TAG, HOMA-IR and BMI, which were positively associated with the degree of NAFLD. Conclusions: Adherence to the DASH diet was independently associated with a marked lower prevalence of NAFLD in Chinese adults, especially in women and those without abdominal obesity, and might be mediated by reducing RBP4, hs-CRP, TAG, HOMA-IR and BMI.